HEMATO-BIOCHEMICAL TREND IN STALL HOUSED HORSES UNDER HOT AND HUMID CLIMATIC CONDITIONS OF ODISHA, INDIA - S. Kanungo; C. R. Pradhan; L.K. Babu; B. Jena; D. P. Das (Exploratory Animal and Medical Research, 2017)
Blood is an important and reliable medium for assessing the health status and performance level of horses. Variations in hematological parameters in horses are associated with several factors such as exercise and training, feeding, age, sex, breed, diurnal and seasonal variation, temperature and the physiological status etc. The objective of this study was to determine the influence of exercise on hematological indices in horses maintained under hot and humid climatic conditions of Odisha, India. Blood samples were drawn from jugular veins of the animals in the morning and 30 minutes, 4 hours and 8 hours after exercise. The blood samples were assessed for Total erythrocyte (RBC), Total leucocytes (WBC), Hemoglobin, Packed cell volume (PCV), Mean corpuscular volume, Mean corpuscular hemoglobin, Mean corpuscular hemoglobin concentration, Erythrocyte Sedimentation rate, Serum total glucose, Whole blood glucose, Serum Sodium, Serum Potassium, Serum Calcium, Serum magnesium and Serum chloride before and after exercise.